A Mankiw's "puzzle": Is durable consumption declining? - Paweł Felis; Henryk Rosłaniec (Contemporary Economics, 2019)
Mankiw's puzzle of long-term (durable) consumption is a significant topic that needs to be solved. We statistically analyze a time series sample from Germany and from the Czech Republic (2004Q1 to 2016Q4). Furthermore, we discussed the analyses that have been performed to date for the USA and France. These analyses have verified the Mankiw's puzzle theory about the problematic evolution of durable consumption expenditures. The verification itself has led to arguments for the initiation of scrapping old cars in France and many other European countries in the 1990s (mainly the Juppe and then the Balladur administrations in France). Currently, when we experience economic booms, it is important to ask what happens in a recession. (The Czech Republic pulled through one mainly due to the automotive industry.) Furthermore, this recession is strengthened if the depreciation rate is much lower than the growth rate of durable consumption. These factors together could cause durable consumption to stagnate. We disproved Mankiw's puzzle theory using a data sample from the Czech Republic and Germany. This conclusion means that long-term consumption does not disappear. The results of the analysis argue against the initiation of scrapping old cars based on current data. The main explanation of the different conclusions of our analysis and the original analysis is that, currently, the new cars that are sold each year have massive innovations. We have to take into account that the new cars that are sold every year satisfy deeper and wider individual needs. The previous conclusion is extended, owing to the initialization of e-mobility and the shorter lifespans of electronic devices.
Keywords: E21; E62; 330; Durable consumption; ARMA stochastic process; Scrapping subsidy; Mankiw's puzzle